Activation of the lytic program of the Epstein–Barr virus in Burkitt's lymphoma cells leads to a two steps downregulation of expression of the proapoptotic protein BimEL, one of which is EBV-late-gene expression dependent - Oussaief, Lassad (2009)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 2009